(untitled) (Economic studies journal, 2021)
Abstract This paper aims to shed light on the subsistence level of wages theory, which its importance has increased after this stream of American studies that dealt with the issue of market concentration, in both markets: commodity market and labor market, and their linkages to low wages. It also aims to strengthen and support the labor effort to reform the structure of the labor market. In order to improve the standards of fairness in the product distribution. The paper dealt with the subsistence level theory in its original form, and then presented an expanded form of it, as well as a new interpretation of the factors behind the stability of the general level of wages at the subsistence level. It focused also on that the main factor behind the stability of wages at the subsistence level is the spread of collusion in the prevailing markets, whether the market for goods and services or labor market. Whereas it causes market transition from competitive forms to monopolistic ones. It also addressed the view stated that the general level of wages in developed countries exceeds the subsistence level, and clarified the reasons behind it, and emphasized that once those reasons disappeared, wages will return to the subsistence level. Not to mention that subsistence level of wages is prevailed in periphery or developing countries. The paper concluded that subsistence level of wages has been prevailed in the labor markets. And to get rid of that, it is necessary to reduce collusion and monopoly in both mentioned markets, as well as adopting Islamic formulas to participate in economic projects; such as Mozarah, Modarabh,..etc.